Herpes simplex virus type 1 epidemiology in the Middle East and North Africa: systematic review, meta-analyses, and meta-regressions - Sonia Chaabane (3574202) (2019)
This study aimed at characterizing herpes simplex virus type 1 (HSV-1) epidemiology in the Middle East and North Africa (MENA). HSV-1 records were systematically reviewed. Findings were reported following the PRISMA guidelines. Random-effects meta-analyses were implemented to estimate pooled mean HSV-1 seroprevalence. Random-effects meta-regressions were conducted to identify predictors of higher seroprevalence. Thirty-nine overall seroprevalence measures yielding 85 stratified measures were identified and included in the analyses. Pooled mean seroprevalence was 65.2% (95% CI: 53.6–76.1%) in children, and 91.5% (95% CI: 89.4–93.5%) in adults. By age group, seroprevalence was lowest at 60.5% (95% CI: 48.1–72.3%) in <10 years old, followed by 85.6% (95% CI: 80.5–90.1%) in 10–19 years old, 90.7% (95% CI: 84.7–95.5%) in 20–29 years old, and 94.3% (95% CI: 89.5–97.9%) in ≥30 years old. Age was the strongest predictor of seroprevalence explaining 44.3% of the variation. Assay type, sex, population type, year of data collection, year of publication, sample size, and sampling method were not significantly associated with seroprevalence. The aprioriconsidered factors explained 48.6% of the variation in seroprevalence. HSV-1 seroprevalence persists at high levels in MENA with most infections acquired in childhood. There is no evidence for declines in seroprevalence despite improving socio-economic conditions. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-018-37833-8